PENGELOLAAN PROGRAM INDUKSI GURU PEMULA (PIGP) DI SMP NEGERI 3 KUNDURAN BLORA - Sugiyarti, S.; Sumarjoko, Bambang (Sebelas Maret University (UNS), 2018)
The method used in the study was a qualitative research for this study aimed to describe the planning, implementation, and evaluation of programs induction of beginning teachers in SMP Negeri 3 Kunduran. Data were collected by interview, observation, and documentation. Validity of the data with data triangulation. Data analysis techniques with data collection, data reduction, data presentation and conclusion. The results of this study stated that the planning PIGP planned jointly by the school principal and guidance counselor. Implementation PIGP in the second to the ninth month, in which the novice teachers implement instructional tahab accompanied by a tutor with evaluation performed at least once a month by the supervising teacher. The final evaluation was conducted in the tenth and eleventh by a guidance counselor, school principals and supervisors to determine the continuation of a career profession beginner teachers.